Key aspects of TaG's argumentation remain unsubstantiated, so their thesis requires further detailed analysis and a broader empirical foundation. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Key aspects of TaG's argumentation remain unsubstantiated, so their thesis requires further detailed analysis and a broader empirical foundation.
iso-id: iso:argument:AVrj5AqY; sha256: sha256:7f9dc8e9f1adac56907196175086242b998fd5bcbb4428278fa68d63c1d7cca8